2021
DOI: 10.1177/13591053211059386
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the characteristics of interventions that promote physical activity in adults with asthma

Abstract: Physical activity is promoted in the asthma population through pulmonary rehabilitation, but limited funding and facilities are available. This review aimed to examine the effectiveness of interventions that promote physical activity and identify the behaviour change techniques (BCTs) and other intervention components used. Five databases were searched, and 25 studies met the inclusion criteria. Interventions had a significant positive effect on physical activity, sedentary behaviour, quality of life and asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 116 publications
(198 reference statements)
2
15
0
1
Order By: Relevance
“…Freitas et al, on the other hand, demonstrated the short-term effectiveness of supervised exercise training (two 60-minute sessions of moderate-vigorous intensity aerobic and resistance exercises per week) 29,30 combined with a weight-loss programme, in increasing PA (steps/day and time spent undertaking MVPA and light-intensity PA) in obese adults with moderate-severe asthma compared to a weight-loss programme alone. This is consistent with the findings of the recent review by Tyson et al 36 . In this review, effective PA interventions in the general asthma population typically comprised of aerobic exercise and/or resistance/strength training of 30-60minutes in duration, 2-3 times a week 9 .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Freitas et al, on the other hand, demonstrated the short-term effectiveness of supervised exercise training (two 60-minute sessions of moderate-vigorous intensity aerobic and resistance exercises per week) 29,30 combined with a weight-loss programme, in increasing PA (steps/day and time spent undertaking MVPA and light-intensity PA) in obese adults with moderate-severe asthma compared to a weight-loss programme alone. This is consistent with the findings of the recent review by Tyson et al 36 . In this review, effective PA interventions in the general asthma population typically comprised of aerobic exercise and/or resistance/strength training of 30-60minutes in duration, 2-3 times a week 9 .…”
Section: Discussionsupporting
confidence: 94%
“…The second aim of this review was to examine the effect of PA interventions on asthma-and health-related outcomes. The findings of our meta-analyses demonstrated an overall positive effect of PA interventions on exercise capacity, asthma control and HRQoL in individuals with moderate-to-severe asthma, which complements previous reviews 16,17,36 . Interestingly however, of the two studies we identified that reported significant improvements in PA in favour of the intervention, only Freitas et al reported a significant improvement in clinical outcomes 29,30 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations